Transition Metal and Inner Transition Metal Catalyzed Amide Derivatives Formation through Isocyanide Chemistry - Shiri, Morteza; Farajinia-Lehi, Noushin; Salehi, Parvin; Tanbakouchian, Zahra (Synthesis, 2020)
The synthesis of amides is a substantial research area in organic chemistry because of their ubiquitous presence in natural products and bioactive molecules. The use of easily accessible isocyanides as amidoyl (carbamoyl) synthons in cross-coupling reactions using transition metal and inner transition metöal catalysts is a current trend in this area. Isocyanides, owing to their coordination ability as a ligand and inherent electronic properties for reactions with various partners, have expanded the potential application of these transformations for the preparation of novel synthetic molecules and pharmaceutical candidates. This review gives an overview of the achievements in isocyanide-based transition metal and inner transition metal catalyzed amide formation and discusses highlights of the proposed distinct mechanisms.1 Introduction2 Synthesis of Arenecarboxamides3 Synthesis of Alkanamides4 Synthesis of Cyclic Amides5 Formation of Alkynamides6 Formation of Acrylamide-like Molecules7 Formation of Ureas and Carbamates8 Conclusion
Keywords: isocyanides; transition metal catalysis; cascade reaction; insertion; amide; cross coupling; multicomponent reaction